XÁC ĐỊNH BIẾN LOẠI CỦA FELDSPAR TRONG PEGMATIT GRANIT MINH TIẾN, LỤC YÊN - Thuyết, Nguyễn Thị Minh; Nhung, Ngụy Tuyết (Vietnam Journal of Earth Sciences, 2012)
To determine varieties of the k-feldspar of pegmatite from Minh Tien, LucYen Amazonite or “amazon stone” is a bright to dark green (with some bluish hue) variety of microcline mineral. The results of XRD, XRF, and petrographic microscopy have confirmed appearance of amazonite in Luc Yen, North West of Vietnam. They are characterized by the variety of microcline that includes intermediate microcline and ordered albite with according parameters: Or = 77.97 to 83.08, Ab = 16.16 to 10.88 and An is 0.25 to 0.2. Moreover, the crystal of amazonite is in big size (usually greater than 1 cm even larger 10cm). They are pale and light green, opaque to semitransparent. Especially, the content of Pb is medium (832 - 872ppm), the content of rare elements (Cs, Rb) are high that changed from 506 to 1089, 6117 to 9262 ppm respectively. All above characteristics imply that variety of Minh Tien Kfeldspar is an usual amazonite.